2015
DOI: 10.1159/000444754
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein-Coupled Receptor 35 Mediates Human Saphenous Vein Vascular Smooth Muscle Cell Migration and Endothelial Cell Proliferation

Abstract: Vascular smooth muscle cell (VSMC) migration and proliferation is central to neointima formation in vein graft failure following coronary artery bypass. However, there are currently no pharmacological interventions that prevent vein graft failure through intimal occlusion. It is hence a therapeutic target. Here, we investigated the contribution of GPR35 to human VSMC and endothelial cell (EC) migration, using a scratch-wound assay, and also the contribution to proliferation, using MTS and BrdU assays, in in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…(), assuming that CID‐2745687 was actually acting via GPR35 in these studies. However, in a more positive context, in isolated human saphenous vein smooth muscle cells, GPR35 agonist‐induced cell lengthening and cell migration were both blocked effectively by concentrations of both CID‐2745687 and ML‐145 consistent with reports on the affinity of these ligands at human GPR35, as defined from in vitro studies (McCallum et al, ), as was proliferation of human saphenous vein endothelial cells (McCallum et al, ).…”
Section: Gpr35: Ligand Pharmacology and Species Variationsupporting
confidence: 67%
See 1 more Smart Citation
“…(), assuming that CID‐2745687 was actually acting via GPR35 in these studies. However, in a more positive context, in isolated human saphenous vein smooth muscle cells, GPR35 agonist‐induced cell lengthening and cell migration were both blocked effectively by concentrations of both CID‐2745687 and ML‐145 consistent with reports on the affinity of these ligands at human GPR35, as defined from in vitro studies (McCallum et al, ), as was proliferation of human saphenous vein endothelial cells (McCallum et al, ).…”
Section: Gpr35: Ligand Pharmacology and Species Variationsupporting
confidence: 67%
“…This has been assessed in experiments measuring agonist‐induced binding of [ 35 S]GTP[S] to an introduced epitope‐tagged form of Gα 13 (Jenkins et al, ) and in assays employing a chimeric Gα q /Gα 13 G protein that allows receptor interaction with Gα 13 to be converted into elevation of intracellular Ca 2+ levels (Jenkins et al, ). Moreover, in human saphenous vein smooth muscle cells, GPR35 agonist‐induced cell migration is inhibited by each of two mechanistically distinct Rho‐kinase inhibitors (McCallum et al, ). Although activation of Gα 13 does not directly regulate levels of secondary messengers, it does regulate Rho‐guanine nucleotide exchange factors.…”
Section: Gpr35: Signalling Mechanismsmentioning
confidence: 99%
“… 15 Functionally, it is demonstrated that GPR35 mediates smooth muscle cell migration and endothelial cell proliferation. 16 GPR35 also induces hypoxia-inducible factor-1 alpha to regulate cellular processes. 17 Besides, GPR35 is identified as a susceptibility gene associated with chronic anthracycline-induced cardio-toxicity in pediatric cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Research have shown that phenotypic transition of VSMC drives the progression of vascular diseases, such as atherosclerosis, diabetes, restenosis, and hypertension [ 11 ]. VSMCs are associated with vessel injury and remodeling in the proinflammatory environment [ 12 , 13 ]. In the normal vessel wall, VSMCs are static, differentiated, contractile and have low rate of proliferation, and express high levels of contractile proteins such as α-smooth muscle actin (α-SMA) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%